Pendampingan Strategi Pemasaran pada UMKM untuk Meningkatkan Efektivitas Penjualan Berbasis Digital Marketing - Ariandi, Muhamad Amir; Rinaldi, Muhammad (Jurnal Nusantara Mengabdi, 2025)
Purpose: This community service program aims to support Micro, Small, and Medium Enterprises (UMKM) in developing and implementing digital marketing strategies. As a key pillar of Indonesia’s economy, many UMKM still rely on traditional marketing methods, which are less effective in reaching broader markets. Methodology/approach: The program was conducted in several stages: preparation, socialization, training, direct mentoring, evaluation, and monitoring. Participants were trained to use digital platforms such as Instagram, Facebook, and TikTok. Data were collected through surveys and interviews conducted before and after the program. Results/findings: The program significantly improved participants’ understanding and skills in digital marketing, content creation, platform management, and data analysis. UMKM successfully developed and implemented structured marketing strategies tailored to their businesses. Conclusion: This initiative effectively enhanced the digital marketing capabilities of UMKM, enabling them to shift from conventional methods to data-driven digital approaches. Structured mentoring was crucial to successful implementation. Continued support and monitoring are recommended to sustain the program’s impact and further boost UMKM competitiveness. Limitations: The program involved a limited number of participants, which may affect the generalizability of the findings. Contribution: The program contributes to strengthening UMKM digital literacy and marketing effectiveness through practical training and mentoring. It also encourages collaboration and knowledge-sharing among local entrepreneurs, supporting their growth in the digital economy.